Unable to Inhale in an Historical Square - Atik, Damla; Keleş, Emine; Bayrak, Gökçen (European Journal of Sustainable Development, 2018)
Livable and sustainable cities are required to respond space-activity necessities of people as much as to provide satisfaction of users in terms of social and physiological ways. Urban squares definitely attract the attention among urban spaces that having significant place in city fiction and life. It is possible to consider squares which were identified with various names through history as “inhalation yards” of a city. Been shaped by culture, life style and expectations of the society whom they belong; squares have importance to obtain sustainability in developing and growing cities. Edirne as a medium scaled city is located in the north-west part of Turkey; have country borders with Greece and Bulgaria; had been capital city of Ottoman Empire almost a century though has cultural and historical wealth. The most significant square of the city is Cumhuriyet Square and it is located in the historical city center. The square has transferred almost all of its facilities and functions to the Saraçlar Street neighbor on, being precluded by traffic axis at the present time. It is aimed to draw attention on cultural and historical traces of the city by scrutinizing the square in terms of usage and meaning in this study. Data will be obtained by evaluating socio-economic, cultural and physical changes of the city and improving project will be suggested for sustainability and future. It is predicted that this suggestion (or inspiring new projects) will be made actual by further surveys providing contribution of society as well as support of administrators who are claiming similar approaches. Keywords: Urban square, urban sustainability, cultural sustainability, historical center, Edirne, Cumhuriyet Square, Atatürk Statue